Recurrent training rejuvenates and enhances transcriptome and methylome responses in young and older human muscle - Sara Blocquiaux; Monique Ramaekers; Ruud Van Thienen; Henri Nielens; Christophe Delecluse; Katrien De Bock; Martine Thomis (Wiley, 2022)
Abstract Background The interaction between the muscle methylome and transcriptome is understudied during ageing and periods of resistance training in young, but especially older adults. More information is needed on the role of retained methylome training adaptations in muscle memory to understand muscle phenotypical and molecular restoration after inactivity or disuse. Methods We measured CpG methylation (microarray) and RNA expression (RNA sequencing) in young (n = 5; age = 22 ± 2 years) and older (n = 6; age = 65 ± 5 years) vastus lateralis muscle samples, taken at baseline, after 12 weeks of resistance training, after training interruption (2 weeks of leg immobilization in young men, 12 weeks of detraining in older men) and after 12 weeks of retraining to identify muscle memory‐related adaptations and rejuvenating effects of training. Results We report that of the 427 differentially expressed genes with advanced age (FDR < 0.1), 71% contained differentially methylated (dm)CpGs in older versus young muscle (FDR < 0.1, M‐value difference >0.4). The more dmCpGs within a gene, the clearer the inverse methylation-expression relationship. Around 73% of the age‐related dmCpGs approached younger methylation levels when older muscle was trained for 12 weeks. A second resistance training period after training cessation increased the number of hypomethylated CpGs and upregulated genes in both young and older muscle. We found indication for an epi‐memory within pro‐proliferating AMOTL1 in young muscle and mechanosensing‐related VCL in older muscle. For the first time, we integrate muscle methylome and transcriptome data in relation to both ageing and training‐induced/inactivity‐induced responses and identify focal adhesion as an important pathway herein. Conclusions This preliminary evidence indicates that previously trained muscle is more responsive to training than untrained muscle at methylome and transcriptome level and recurrent resistance training can partially restore ageing‐induced methylome alterations.